Produksi Tanaman Ubi Jalar Ungu dan Rumput Gajah Odot pada Sistem Tanam Tumpangsari dengan Jarak Tanam Berbeda - Asmoro, Zherlin; Widjajanto, D.W.; Sumarsono, Sumarsono (UNIVERSITAS LABUHANBATU, 2022)
The aim of the study was to examine the treatment of purple sweet potato spacing and elephant grass cv. Odot (Pennisetum purpureum cv. Mott) spacing on the production of purple sweet potato and elephant grass cv. Odot. Field experiment was conducted in Kalongan Village, East Ungaran Sub-district, Semarang District (7o08â€™27â€-7o15â€™72â€Sand 110o40â€™88â€-110o.48â€™14â€ E). Analysis of soil, fertilizer and dry matter of purple sweet potato and elephant grass cv. Odot were carried out at the Ecology and Plant Production Laboratory, Department of Agriculture, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang from March to August 2021. A 2 x 4 factorial experiment based a randomized block design with 3 replications was used throughout the experiment. The first factor was the spacing of purple sweet potatoes consisted of V1: 90 cm x 30 cm, V2: 90 cm x 40 cm, V3: 90 cm x 50 cm and V4: 90 cm x 60 cm. The second factor was the spacing of elephant grass cv. Odot, namely T1: 90 x 60 cm and T2: 90 x 45 cm. The data obtained were statistically analyzed using analysis of variance (ANOVA) and significantly different parameters were tested by Duncan's Multiple Distance Test at 5% level. The results showed that the spacing of purple sweet potato and spacing of elephant grass cv. Odot had no significant effect on the production of purple sweet potato but had a significant effect on the production of elephant grass cv. Odot. Based on the results of the competition index, it was concluded that the purple sweet potato plant was more dominant than the elephant grass cv. Odot.Â Keywords : dry matter production, intercropping, Pennisetum purpureum cv. Mott, sweet potato